Volume 7B: Structures and Dynamics 2014
DOI: 10.1115/gt2014-26295
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis and Validation of the Rotor Blade Vibration Response Induced by High Pressure Compressor Deep Surge

Abstract: The following paper presents a numerical analysis of a deep surge cycle of a 4.5 stage research compressor. The resulting unsteady loads are used to determine the response of two particular rotor blade rows that are then compared to strain gauge data from measurements. Within a deep surge cycle the compressor experiences a rapid change of the flow field from forward to reversed flow. This rapid breakdown is linked to a new mean blade load. Hence, the rapid change in blade loads are able to excite fundamental b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…of surge highlighted. Three-dimensional URANS simulations of post-stall transients require very large computational power and most models found in recent publications have attempted to reduce the size of the domain, for example by modelling a single passage (Giersch et al, 2014), part of the annulus (Crevel et al, 2014), or using a hybrid backward difference formula/harmonic balance method (Sun et al, 2019). Full-annulus URANS simulations have been carried out by (Zhao et al, 2018) using the code AU3D, which successfully modelled a deep surge event and full-span rotating stall of a modern, high-speed, multi-stage, core compressor.…”
Section: Figure 1 -Example Of Rotating Stall and Deep Surge Trajectormentioning
confidence: 99%
“…of surge highlighted. Three-dimensional URANS simulations of post-stall transients require very large computational power and most models found in recent publications have attempted to reduce the size of the domain, for example by modelling a single passage (Giersch et al, 2014), part of the annulus (Crevel et al, 2014), or using a hybrid backward difference formula/harmonic balance method (Sun et al, 2019). Full-annulus URANS simulations have been carried out by (Zhao et al, 2018) using the code AU3D, which successfully modelled a deep surge event and full-span rotating stall of a modern, high-speed, multi-stage, core compressor.…”
Section: Figure 1 -Example Of Rotating Stall and Deep Surge Trajectormentioning
confidence: 99%
“…Another publication [17] continued this development and demonstrated good agreement between the properties of optically recorded blades and experimental vibration measurements. Some research studies have also appeared in the field of aircraft and automotive turbochargers [18,19], but their results are not very applicable, particularly with regard to the point of identification of the mistuning and the cause of the mistuning of marine engine turbocharger bladed discs.…”
Section: Introductionmentioning
confidence: 99%
“…In this study part-span rotating stall was observed across a range or rotational speeds and VSV settings. Another experimental activity was performed at DLR (the German Aerospace Center), where performance and mechanical loads during surge were measured on a high-speed IPC [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This approach, although it offers the best accuracy and fidelity, is still too computational expensive to be used for multiple simulations or the creation of rotating stall characteristics. An attempt was also made to create a complete compressor map using AU3D [7]. However, to reduce computational cost, only a single passage was modelled; the rotating stall characteristic was then only approximated, as rotating stall could not be actually modelled.…”
Section: Introductionmentioning
confidence: 99%